2006
DOI: 10.1590/s1516-44462006000600003
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre homicídio e transtornos mentais

Abstract: Relationship between homicide and mental disordersRelação entre homicídio e transtornos mentais A b s t r a c t Objective: Several studies have found a relationship between severe mental disorders and violence. One of the approaches to study this theme are investigations with homicide offenders. The aim of the present article was to investigate the association between homicide and mental disorders. Method: A review of the literature was made through the following databases: Medline, Scientific Eletronic Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
2
12
0
15
Order By: Relevance
“…Impulsive behavior and anger management issues, as well as a lack of social abilities, were also cited as important factors by Valenc¸a et al 22,33,34 This is in agreement with our findings, particularly in regard to the risk of new violent behavior, and might warrant the adoption of widespread strategies to reduce this risk factor. Social and environmental factors were also found to have a strong correlation, particularly drug addiction, a personal history of abuse, and lack of family support.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Impulsive behavior and anger management issues, as well as a lack of social abilities, were also cited as important factors by Valenc¸a et al 22,33,34 This is in agreement with our findings, particularly in regard to the risk of new violent behavior, and might warrant the adoption of widespread strategies to reduce this risk factor. Social and environmental factors were also found to have a strong correlation, particularly drug addiction, a personal history of abuse, and lack of family support.…”
Section: Discussionsupporting
confidence: 92%
“…These data corroborate previous findings. [20][21][22]24,26,30,33,34 Mecler 1,2 found similar results in an analysis of dangerousness cessation examinations. As was the case in our study, that investigator found that important factors had been left out of a large number of dangerousness cessation reports, such as personal history and criminal background, as well as the nature of the offenses.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Estudos recentes têm demonstrado que existe associação entre violência e doença mental [8][9][10][11][12][13][14][15] . As evidências apontam que portadores de transtornos psiquiátricos -particularmente os transtornos: orgânico cerebral, de personalidade, por causa de uso de substâncias psicoativas e esquizofrenia -são mais propensos a cometerem crimes violentos do que a população geral.…”
Section: Discussionunclassified
“…Os portadores de doenças mentais constituem população com maior tendência a comportamento criminoso [8][9][10][11][12][13][14][15] . Os psiquiatras são freqüentemente solicitados a avaliar o risco relacionado a estas populações.…”
Section: Discussionunclassified